Polymorphisms of RIG‐I‐like receptor influence HBV clearance in Chinese Han population. Issue 8 (3rd April 2021) - Yao, Yinan; Shen, Yan; Shao, Haifeng; Liu, Yuchang; Ji, Yan; Du, Guoming; Ye, Xiangyu; Huang, Peng; Chen, Haiming
Highlights: The participants were all infected with HBV alone and treatment‐naïve. DDX58 rs3824456, rs2074160 and IFIH1 rs2111485 polymorphisms were associated with HBV spontaneous clearance. The associations were discovered in Chinese Han populations for the first time. Abstract: Retinoic acid‐inducible gene I‐like receptors (RLRs) play an essential role in human innate immune, which may influence the spontaneous clearance of hepatitis B virus (HBV) infection. We aimed to investigate whether the SNPs in RLR family were associated with HBV spontaneous clearance. The current study included 82 participants with spontaneous clearance, 601 asymptomatic hepatitis B surface antigen (HBsAg) carriers, and 168 participants with chronic hepatitis B (CHB). Six SNPs ( DDX58 rs3824456, rs3205166, DHX58 rs2074160, rs2074158, IFIH1 rs2111485, rs3747517) were genotyped to explore their association with HBV spontaneous clearance. Patients carrying the mutant allele C at rs3824456 or A at rs2074160 were more likely to achieve spontaneous clearance compared with asymptomatic HBsAg carriers (additive model: odds ratio [OR] = 0.69, 95% confidence interval [CI] =  0.49–0.97; dominant model: OR = 0.54, 95% CI = 0.31–0.95, respectively). In addition, patients carrying the mutant allele G at rs2111485 were more likely to achieve spontaneous clearance compared with CHB (dominant model: OR = 0.47, 95% CI = 0.25–0.87). The mutations were protective factors for HBV spontaneous clearance. These results suggest the DDX58 rs3824456, DHX58 s2074160, IFIH1 rs2111485 were associated with spontaneous clearance of HBV, which may be predictive markers in the Chinese Han population of HBV.